Carbon footprint of the cultivation of roses in Ecuador comparing two methodologies: GHG Protocol vs. PAS 2050 - Guallasamin Constante, Karina (2018)
Ecuador is the third largest exporter of roses worldwide. A key factor for the international competitiveness is to calculate and reduce greenhouse gases (GHG). For this reason, we calculated the carbon footprint (CF) of the cultivation of roses in Ecuador, taking as a case study the Company Ecoroses S.A. in the year 2015. The company is located in the canton Mejia, province of Pichincha, and dedicates 100% of its production to roses. The CF was calculated using two methodologies, GHG Protocol and PAS 2050, considering the limits of the system “from the cradle to the door”. The emission factors were compiled from international databases such as IPCC and Ecoinvent v2.2. The result of the CF was 3,75 kg CO2eq/kg of rose exported. The three sources of emission of GHG that most affect are: agricultural products (37,7%), electrical energy (13,3%), and the use of fossil fuels (10,95%). This CF doubles that of dry cocoa, and is more than 8 times higher than that of domestic bananas. Therefore, the implementation of good environmental practices is proposed to reduce GHG, specifically, organic fertilizers, energy saving, and biofuels.